Mejoramiento del suelo cohesivo por medio de la compactación dinámica (2015)
Dynamic compaction is a patented method developed in 1969 by the French engineer Lous Menard. Dynamic compaction is a technique that involves the densification of soil using the energy of impact waves that produces the free fall of a heavy plate (200 tons) from high altitudes between 15 and 60m. The energy of the impact produces the densification of the soil improving its mechanical and dynamic properties; in granular and cohesive soils, below and above the water table, both on land and in the high seas. The reaction of the soil to dynamic compaction depends on its geotechnical characteristics and the amount of energy applied by the impacts of the platen. The energy is a function of the mass, the height of fall and the number of falls at each point. By employing a system such as the one described, it is possible to triple the carrying capacity, the California Bearing Ratio (CBR) and reduce the elastic settlement and settlement by consolidation considerably. The variety of types of material successfully densified by means of dynamic compaction is very broad; effective improvement has been achieved in materials ranging from rock fillings to cohesive and saturated soils through construction debris. An improvement of cohesive soil by means of dynamic compaction in a lot located at kilometer 6.5 via Bogotá Medellín south side of Celta Trade Park was carried out as an application of the present work. A planning of striking patterns, dissipation time of the pore pressure, number of passes, height of fall and weight of the stage was made. Before, during and after the compaction work, the density increase was checked by means of: cutting wave velocities, compression speed, soundings and laboratory tests. By correlations with the sonars, the wave velocities corresponding to the desired densities were determined and, thus, it was found that the desired degree of compaction had been reached. The results of the improvement are immediate, depressions were reached in the surface of the land up to 1.9m with 27 strokes per point.